Early childhood vaccination and subsequent mortality or morbidity: are observational studies hampered by residual confounding? A Danish register-based cohort study - Andreas Jensen; Per Kragh Andersen; Lone Graff Stensballe (BMJ Open)
Objectives To estimate the association between childhood vaccination and subsequent morbidity and mortality by adjusting for environmental and host factors. Further, to examine the degree of residual confounding in such observational studies.Design Register-based cohort study including 1 122 929 Danish children.Participants All children born in Denmark in the period 1999–2016 who survived until 16 months of age without prior migration followed from 16 months until the first of the following: event of interest, migration, 5 years of age or 31 December 2016.Main outcome measures Adjusted HRs (aHRs) and absolute risks were calculated for the three outcomes: mortality, hospitalisation for infection and asthma using register data on deaths, specific hospital contacts and dispensed prescribed medication. The exposure was the combination of the routine vaccines against diphteria–tetanus–pertussis–polio–Haemophilus influenzae type b and measles–mumps–rubella (DTP and MMR in short) administered in early childhood. Hospitalisation due to accidents was analysed as a negative control outcome to examine residual confounding.Results Children with 3DTP+MMR had a lower hazard of mortality than the reference group with 3DTP, adjusted HR (aHR)=0.45 (95% CI: 0.35 to 0.57), whereas the children with 1 or 2 DTP had higher hazards of dying, aHR=1.55 (95% CI: 1.14 to 2.13) and aHR=1.96 (95% CI: 1.34 to 2.89). The vaccination group 3DTP+MMR was associated with a reduced hazard of asthma aHR=0.94 (95% CI: 0.92 to 0.96). Also, the vaccination group 3DTP+MMR was associated with a reduced hazard of hospitalisation due to accidents, aHR=0.83 (0.80 to 0.85) compared with the reference group with 3 DTP.Conclusions The results suggested a beneficial impact of MMR on under-five mortality but did not support the hypothesis that DTP is detrimental, since the group of children with fewer DTP vaccinations experienced increased mortality. The results of the study may to some degree be prone to residual confounding since an unexpected association between MMR vaccination and hospitalisation for accidents was observed.